2015
DOI: 10.3109/0886022x.2015.1010989
|View full text |Cite
|
Sign up to set email alerts
|

Attachment style predict compliance, quality of life and renal function in adult patients after kidney transplant: preliminary results

Abstract: Aim: Aim of this study was to evaluate the association between attachment style, compliance, quality of life and renal function in adult patients after kidney transplantation. Methods: A total of 43 adult patients who received a kidney transplant more than 3 months before were enrolled and were asked to complete two Self-Report questionnaires: Attachment Style Questionnaire (ASQ-40) and Short Form Health Survey (SF-36). Also compliance was measured using appropriate questions. Results: Linear regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
(9 reference statements)
0
22
0
Order By: Relevance
“…In addition, there are a number of articles in literature that focus on the psychological aspects affecting graft survival and compliance that could also apply to living kidney donation. 20,21 We also noticed that trend but did not analyze it in our manuscript. Therefore, our findings require further validation by longer prospective studies involving a larger sample size across multiple clinical centers involving more donor-recipient pairings including father-to-child and mother-to-child parings, as well as preand postoperative psychological aspects of recipients.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, there are a number of articles in literature that focus on the psychological aspects affecting graft survival and compliance that could also apply to living kidney donation. 20,21 We also noticed that trend but did not analyze it in our manuscript. Therefore, our findings require further validation by longer prospective studies involving a larger sample size across multiple clinical centers involving more donor-recipient pairings including father-to-child and mother-to-child parings, as well as preand postoperative psychological aspects of recipients.…”
Section: Discussionmentioning
confidence: 94%
“…It has also been outlined that coping strategies may be associated with negative compliance among patients who have difficulty in processing emotion [11]. In a previous analysis on the same patients sample population, also some quantitative dimensions of attachment style has been indicated as a predictors of compliance perception and creatinine levels after transplantation [13]. Thus, the role played by emotional pattern in influencing compliance to medical treatment should be taken into consideration during preoperative evaluation [5].…”
Section: Discussionmentioning
confidence: 97%
“…Hence, attachment style could contribute to explain the crucial role of social support in adherence. Calia et al ( 59 ) found that attachment style and adherence were interrelated in kidney recipients. In a more psychodynamic approach, attachment theory aspects, resistance (to treatment), adaptive and maladaptive defense mechanisms in disease coping, and (counter)transference could be therapeutically approached ( 60 ).…”
Section: Discussionmentioning
confidence: 99%